1993
DOI: 10.1007/bf02537075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lovastatin on hepatic fatty acid metabolism

Abstract: The in vitro and in vivo effects of lovastatin on fatty acid metabolism were studied in isolated rat hepatocytes. When added in vitro to cell incubations, lovastatin stimulated de novo fatty acid synthesis and acetyl-CoA carboxylase activity, whereas fatty acid synthase activity was unaffected. Lovastatin depressed palmitate, but not octanoate, oxidation. This may be attributed to the lovastatin-induced increase in intracellular malonyl-CoA levels, as no concomitant change of carnitine palmitoyltransferase I (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…ACC produces malonyl-CoA substrate for fatty acyl CoA synthase (FAS), a committed enzyme for fatty acid biosynthesis [20]. Interestingly, a study showed that lovastatin enhances fatty acid biosynthesis in cultured hepatocytes by activating ACC [54]. Our study is thus consistent with the enhancement of ACC activity in SH-SY5Y cells by SIM as indicated by a decrease in its phosphorylation.…”
Section: Discussionsupporting
confidence: 87%
“…ACC produces malonyl-CoA substrate for fatty acyl CoA synthase (FAS), a committed enzyme for fatty acid biosynthesis [20]. Interestingly, a study showed that lovastatin enhances fatty acid biosynthesis in cultured hepatocytes by activating ACC [54]. Our study is thus consistent with the enhancement of ACC activity in SH-SY5Y cells by SIM as indicated by a decrease in its phosphorylation.…”
Section: Discussionsupporting
confidence: 87%
“…Acetyl-CoA carboxylases (ACCs) enzymes are involved in the synthesis and oxidation of fatty acids and have been targeted for the treatment of metabolic diseases such as type 2 diabetes and dyslipidaemia 3 .The ACCs inhibition might be expected to decrease fatty acid synthesis and increasing fatty acid oxidation. Studies indicated that high fat diet stimulates ACC1 expression in the liver 6 and another, study indicated that lovastatin increases fatty acid biosynthesis in cultured hepatocytes by activating ACC 39 which are in agreement with our study, but the increase of enzyme expression was not significant (table 5). Some studies have shown that malonyl CoA not only controls fatty acid metabolism but also has an important signaling function through its allosteric inhibition of carnitine palmitoyltransferase 1.…”
Section: Discussionsupporting
confidence: 92%
“…FAS is an enzyme synthesis fatty acids 3 . A study in cultured hepatocytes showed that lovastatin increased fatty acid biosynthesis by activating ACC 44 . Our study indicated that ACC1 mRNA expression is decreased when G4 group is treated by HFD and 20 mg simvastatin (P> 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Because PPAR␣ controls cellular fatty acid ␤-oxidation, we speculate that the unexplained rise in LCFA oxidation activity by statins (40,49,50) is at least in part mediated via PPAR␣ activation. This hypothesis is strongly supported by the fact that the induction of ACO mRNA levels by simvastatin is fully suppressed in PPAR␣-null mice (Fig.…”
Section: Statin-mediated Induction Of L-fabp Gene Expression Is Disrumentioning
confidence: 98%